Optimising Open Educational Resources and practises to Enable Inclusive Education - Madhav, Natasha (Teacher education through flexible learning in Africa, 2024)
Globalisation, technology, innovation, and ever-changing customer needs have created an explosion of information for learners at Higher Education Institutions (HEIs). Developing science, technology, engineering, and mathematics (STEM) skills in students is critical to achieving the United Nations Sustainable Development Goals. However, although African universities have made progress in the quantity and quality of their research output in STEM subjects, the continent continues to lag behind much of the rest of the world. Therefore, engaging students today requires a paradigm shift to promote inclusivity, empower critical thinking, and allow students and educators to co-create knowledge. HEIs in developing countries such as South Africa still face many challenges arising from the digital divide, budget constraints, and increased power cuts. Advancements in online learning have led to new learning practices of using Open Educational Resources (OER). Information and communication technology (ICT) can provide effective and inclusive access to OER that can be used anytime and anywhere. UNESCO, which has been a precursor in advocating for the adoption of OER, has recognised the potential and efficiency of OER not only to permit remote learning but also to enable lecturer and learner collaboration and engagement. As these technologies continue to develop, we can expect to see even more innovative and effective ways to use them for learning. The study explores an open pedagogical approach that enables inclusivity, promotes access, and influences the use of OER tools and technologies by students in the classroom. The results of the outcome could increase awareness of the potential of using open pedagogical approaches to support teaching and learning activities that can enhance and assist educators in integrating technology and drive more inclusive, learner-centred approaches into the curriculum. However, currently, not many HEIs in South Africa are embracing or using OER and open practices effectively.